Defining chronic cancer: patient experiences and self-management needs. Issue 4 (1st December 2015) - Harley, Clare; Pini, Simon; Bartlett, Yvonne Kiera; Velikova, Galina
Abstract : Objective: Chronic cancer is poorly defined and strategies for supporting patients during this disease phase are lacking. This research defines chronic cancer, explores patient experiences and reviews patients' support needs against those described in the 2007 Department of Health Generic Choice Model for Long-term Conditions (DoH-GCM). Design: Semistructured interviews were audio recorded, transcribed and data explored for emergent themes. The a priori themes from DoH-GCM were applied: clinical support; self-care and self-management; supporting independence; psychological support; and social and economic factors. Results: 56 patients >12 months postdiagnosis of advanced cancer were recruited from five clinics at a Yorkshire cancer centre: breast (n=11); renal (n=11); colorectal/gastrointestinal (n=12); gynaecological (n=12); and prostate (n=10). Most patients aspired to living normal lives. Challenges included frequent and lengthy hospital appointments, long-term symptom control and uncertainty. Only renal and prostate patients reported routine access to specialist nursing. Uptake of support services was varied and there was generally poor understanding of support pathways for non-medical problems and issues occurring when patients were not receiving active treatment. There was variation in coping strategies and ability of patients to attain a positive outlook on life. Conclusions: For patients to do well in this cancer phase requires good self-management of symptoms plus taking an active role in accessing appropriate services as needed. Care planning at the point of transition to the chronic phase of cancer should focus on evaluating patients' needs, clarifying support pathways, increasing the profile and involvement of community services and organisations, and supporting patients and families develop effective self-management skills.